Heavy Metal Uptake by Agro based Waste Materials (Global Journal of Science Frontier Research, 2013)
Presence of heavy metals in the aquatic systems has become a serious problem. As a result, there has been a great deal of attention given to new technologies for removal of heavy metal ions from contaminated waters. Biosorption is one such emerging technology which utilized naturally occurring waste materials to sequester heavy metals from industrial wastewater. The aim of the present study was to utilize the locally available agricultural waste materials for heavy metal removal from industrial wastewater. The wastewater containing hexavalent chromium was treated with biomass prepared from corn stalks. It was fund that a time of one hour was sufficient for sorption to attain equilibrium. The equilibrium sorption capacity after one hour was 0.375 mg.g-1. The optimum pH was (2-2.5) for chromium. Ion exchange was the major removal mechanism along with physical sorption and precipitation. The biosorption data was well fitted to Langmuir adsorption model. The kinetics of biosorption process was well described by the pseudo 2nd order kinetics model. It was concluded that adsorbent prepared from corn stalks can be utilized for the treatment of heavy metals in wastewater.
Keywords: heavy metals; chromium; biosorption; langmuir isotherm; freundlich isotherm; kinetic models